Identification of blood erythroid markers useful in revealing erythropoietin abuse in athletes - Magnani, M.; Corsi, D.; Bianchi, M.; Paiardini, M.; Galluzzi, L.; Gargiullo, E.; Parisi, A.; Pigozzi, F. (2001)
Recombinant human erythropoietin (rEpo) is being used with increasing frequency by endurance athletes to improve aerobic potential. Although rEpo administration has been banned by the International Olympic Committee, no methods are available to unequivocally detect its abuse in sports. Prompted by these considerations, we evaluated the main hematological and biochemical modifications measured in the blood of 18 volunteers upon rEpo administration. Different rEpo regimens, iron, folic acid, and vitamin B12 administration did not significantly modify the percentage increase in hematocrit. However, a significant decrease in circulating ferritin (fr) and an increase in the soluble transferrin receptor (sTfr) were not found in athletes receiving low (30 IU/kg) doses of rEpo. Thus, an increase in the sTfr/fr ratio cannot be used as an indicator of rEpo abuse, at least when the hormone is administered at low concentrations. In contrast, the amounts of beta-globin mRNA detected by quantitative competitive (RT)-PCR in whole blood samples significantly increased above the threshold levels in all of the treatments investigated. Taken together, these data suggest that hematocrit value, reticulocyte count, soluble transferrin receptor content, and concentration of beta-globin mRNA, when included in a new multiparametric formula, can detect rEpo abuse in 57.5% of the samples examined with a confidence interval of 99.99%. Thus, the method reported in this paper could significantly improve the tests currently available, which in similar experiments allowed the detection of rEpo abuse in only 7.6% of the samples examined. Blood Cells Mol Dis 2001 May;27(3):559-71